Strengthening Communication Skills through Training Public Speaking Digital Media Based for Members of Karang Taruna Bangkit Jaya Tasikmalaya City. - Kartadireja, Welly Nores; Setiartin, Titin; Rosiana, Shinta; Pitrianti, Siti; Sirait, Budi Chrismanto (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2024)
This service aims to improve the communication skills of members of Karang Taruna Bangkit Jaya in Tasikmalaya City through public speaking training using digital media. By applying this method, it is hoped that Karang Taruna members can develop their public speaking skills effectively and confidently. The training implementation plan will cover various aspects, including public speaking techniques by paying attention to linguistic and non-linguistic aspects, as well as the use of digital media to strengthen communication messages. Training will be structured and interactive, allowing participants to practice hands-on and receive constructive feedback. It is hoped that the result of this training will be an improvement in the communication skills of Karang Taruna members, which will help them in various social activities, organizational activities, and the potential for better self-development. In addition, the use of digital media is expected to enrich the training experience and make participants more interested. This service underscores the importance of developing communication skills in social and organizational contexts, as well as the benefits of implementing digital media as a means to achieve these goals.